1998
DOI: 10.1149/1.1838322
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Processing Parameters in the Low‐Temperature Chemical Vapor Deposition of Titanium Nitride from Tetraiodotitanium

Abstract: Key findings are presented from a systematic study aimed at establishing a fundamental understanding of precursor decomposition pathways and resulting film nucleation and growth kinetics in the chemical vapor deposition of titanium nitride from tetraiodotitanium. As part of the study, key process parameters were varied systematically in order to determine process activation energy and establish corresponding functionality curves for film purity, growth rate, structure, and morphology. The key process parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…For one, they were found to always be rich in nitrogen: the N/Ti ratio was always measured to be above unity (Figure ). In fact, even though most past publications report the deposition of TiN films, in the cases where compositional information has been provided, deviations from N/Ti = 1 can often be seen. ,,, Because these deviations are not large, and because of the uncertainties associated with the measurements of surface concentrations, they have been commonly ignored. Certainly, surface atomic ratios are not very sensitive to changes in film composition and, therefore, are less than ideal as a method to determine the nature of the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, they were found to always be rich in nitrogen: the N/Ti ratio was always measured to be above unity (Figure ). In fact, even though most past publications report the deposition of TiN films, in the cases where compositional information has been provided, deviations from N/Ti = 1 can often be seen. ,,, Because these deviations are not large, and because of the uncertainties associated with the measurements of surface concentrations, they have been commonly ignored. Certainly, surface atomic ratios are not very sensitive to changes in film composition and, therefore, are less than ideal as a method to determine the nature of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Some past studies on TiN deposition have also reported the use of X-ray diffraction techniques for the characterization of the films, ,,,,,, but in none of those were structures other than TiN identified. However, two issues need to be considered here.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methods have been employed for the growth of TiN including atomic layer deposition (ALD), chemical vapor deposition, and magnetron reactive sputtering. Among them, ALD has advantages for plasmonic and TPV applications as it enables exquisitely conformal deposition onto complex 3D photonic structures combined with sub-nanometer control of film thickness. TiN films have previously been prepared by either plasma-enhanced (PE) ALD or thermal ALD process.…”
Section: Introductionmentioning
confidence: 99%
“…A TiN barrier typically failed through grain boundary diffusion. In this respect, TiN deposited by physical vapor deposition (PVD) [Wang, 1990;Kumar, 1988;Hibbs, 1983;Kanamori, 1986;Wu, 1991] and chemical vapor deposition (CVD) [Sherman, 1991;Yuokoyama,1991;Kurtz, 1986; Plasma Assisted Deposition of Ti-Si-N and Ti-Si-N-0 Diffusion Barrier Films Ishihara, 1990;Faltermeier, 1997;Faltermeier, 1998;Hu, 1997] techniques exhibited mostly columnar type morphology (Figure 2-3), with grain boundaries running along the entire thickness of the TiN film. This morphology provided a fast diffusion pathway for copper migration across the barrier to the underlying substrate [Olowolafe, 1992] and leads to a device failure.…”
Section: Titanium Nitridementioning
confidence: 99%
“…This morphology provided a fast diffusion pathway for copper migration across the barrier to the underlying substrate [Olowolafe, 1992] and leads to a device failure. [Faltermeier, 1998]. [Shin, 2004] 350 uX2»cm - [Olowolafe.…”
Section: Titanium Nitridementioning
confidence: 99%